Studi Keunggulan Bersaing UMKM Mebel - Marnoto, Marnoto; Setyadi, Yusuf; Hartarini, Yovita Mumpuni; Adityawan, Adityawan (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the downward trend in the number of furniture MSMEs. Market orientation, entrepreneurial orientation, product innovation, and marketing performance are some of the factors that influence the company's competitive advantage, which results in the sustainability of the company in the future. This study aims to determine the effect of market orientation, entrepreneurial orientation, product innovation, and marketing performance on the competitive advantage of furniture MSMEs. The type of this study is descriptive quantitative correlative with cross-sectional approach. Population and sample used in this study amounted to 35 respondents. The data collection method was carried out through interviews and questionnaires distributed to owners of furniture MSMEs in Guntur District, Demak Regency. The data obtained was then analyzed using multiple linear regression analysis, hypothesis testing with the t test, model feasibility testing with the f test, determination coefficient testing (R2), and classical assumption testing. Based on the results of the t test, it can be concluded that there is a positive and significant effect of market orientation variables, product innovation, and marketing performance on the competitive advantage of furniture MSMEs, while the entrepreneurial orientation variable has a positive but insignificant effect on the competitive advantage of furniture MSMEs